2018
DOI: 10.1038/s41586-018-0519-y
|View full text |Cite|
|
Sign up to set email alerts
|

Necroptosis microenvironment directs lineage commitment in liver cancer

Abstract: Primary liver cancer represents a major health problem. It comprises hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC), which differ markedly with regards to their morphology, metastatic potential and responses to therapy. However, the regulatory molecules and tissue context that commit transformed hepatic cells towards HCC or ICC are largely unknown. Here we show that the hepatic microenvironment epigenetically shapes lineage commitment in mosaic mouse models of liver tumorigenesis. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
280
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(291 citation statements)
references
References 42 publications
8
280
0
3
Order By: Relevance
“…This would suggest that MLKL-dependent necroptosis, eventually through a pathway independent of RIPK3, would protect OTULIN deficient hepatocytes from death by apoptosis. Interestingly, a recent study demonstrated that suppression of necroptosis in hepatocytes could promote hepatocyte apoptosis favoring the development of HCC (Seehawer et al, 2018). This observation suggested that hepatocyte necroptosis generates a liver cytokine microenvironment which promotes the development of intrahepatic cholangiocarcinoma and not HCC from oncogenically transformed hepatic cells (Seehawer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This would suggest that MLKL-dependent necroptosis, eventually through a pathway independent of RIPK3, would protect OTULIN deficient hepatocytes from death by apoptosis. Interestingly, a recent study demonstrated that suppression of necroptosis in hepatocytes could promote hepatocyte apoptosis favoring the development of HCC (Seehawer et al, 2018). This observation suggested that hepatocyte necroptosis generates a liver cytokine microenvironment which promotes the development of intrahepatic cholangiocarcinoma and not HCC from oncogenically transformed hepatic cells (Seehawer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on mice addressed how a hepatic microenvironment, created by two different methods of oncogenic delivery, could influence the type of hepatic tumor [109]. The authors showed that the same oncogenic drivers delivered to mature hepatocytes gave rise to iCCA when embedded in a necroptosis-dominated microenvironment, while an apoptotic milieu favored the development of HCC [40,109]. The necroptosis microenvironment was characterized by specific inflammatory cytokines (e.g., C-C motif ligand 6) secreted from immune cells, which were, in turn, activated by DAMPs released from necroptotically dying hepatocytes [18,40,59].…”
Section: Necroptosis and Cholangiocarcinomamentioning
confidence: 99%
“…(1) The regulatory molecules and tissue context that commit transformed hepatic cells toward HCC or CCA are still largely unknown, but a recent mouse study showed that hepatocytes with aberrantly activated oncogenes give rise to CCA when embedded in a necroptosis-dominated hepatic microenvironment. (65) DAMPs released by necroptotic hepatocytes can activate immune cells to secrete various specific cytokines to form a robust inflammatory environment, determining the outgrowth of CCA from transformed hepatocytes. In contrast, hepatocytes that harbor the same oncogenic driver will give rise to HCC if it is not adjacent to necroptotic hepatocytes.…”
Section: Liver Cancermentioning
confidence: 99%